2016
DOI: 10.2298/sarh1604151k
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anterior cruciate ligament reconstruction on hamstring and quadriceps muscle function outcome ratios in male athletes

Abstract: The assessment of RFD may be considered an objective recovery parameter for one's readiness to return to sports and should be an integral part of standard follow-up protocol for athletes after ACL reconstruction. Moreover, the combination of indices derived from maximal and explosive strength may provide better insight in muscle strength balance, as well as a clear picture of functional implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Interestingly, participants in a study by Pamukoff et al 66 demonstrated full symmetry of knee extensors 4 years after ACLR and RFD deficits were observed only when comparing the ACLR group to an uninjured control group (5%-23%). Between-limb asymmetries in knee flexor RFD were of a moderate-to-high magnitude four to 6 months after ACLR (11%-32%) 71,72 while approaching small-to-moderate magnitude at later time points of 1 65 to 2 58 years after ACLR surgery (5%-13%).…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Interestingly, participants in a study by Pamukoff et al 66 demonstrated full symmetry of knee extensors 4 years after ACLR and RFD deficits were observed only when comparing the ACLR group to an uninjured control group (5%-23%). Between-limb asymmetries in knee flexor RFD were of a moderate-to-high magnitude four to 6 months after ACLR (11%-32%) 71,72 while approaching small-to-moderate magnitude at later time points of 1 65 to 2 58 years after ACLR surgery (5%-13%).…”
Section: Discussionmentioning
confidence: 91%
“…The present systematic review suggests that between-limb asymmetries in RFD after ACLR may persist for several years post-operatively for both the knee extensors and the knee flexors. Between-limb asymmetry in the knee extensor RFD (26%-57%) was highest four to 7 months post-ACLR 56,59,69,71,72 and decreased through to 1 year after ACLR 65 (knee extensor RFD asymmetry 21%-29%). Knee extensor RFD asymmetry was still present 2 58 (20%-23%) to 4 years 63,67 (11%-22%) after ACLR.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations